2001
DOI: 10.2337/diabetes.50.3.637
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Gene for IGF-I

Abstract: Evidence is accumulating that low levels of IGF-I play a role in the pathogenesis of type 2 diabetes and cardiovascular diseases. We examined the role of a genetic polymorphism in the promoter region of the IGF-I gene in relation to circulating IGF-I levels and growth measured as body height, and we studied the relationship of this polymorphism with type 2 diabetes and myocardial infarction. The relation between the IGF-I polymorphism and body height was assessed in a populationbased sample of 900 subjects fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
335
9
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(380 citation statements)
references
References 32 publications
(20 reference statements)
31
335
9
4
Order By: Relevance
“…Of the six IGFBPs fully characterised, IGFBP-1 is considered to be the principal hour-to-hour regulator of circulating IGF activity [14], forming the link between dietary ingestion, glucose metabolism and the IGF axis. We and others have established close links between the IGF system and the development of impaired glucose tolerance, obesity and macrovascular disease [15][16][17][18]. In a white European population, we demonstrated that such changes predict the development of worsening glucose tolerance at the 5-year follow-up [6].…”
Section: Introductionsupporting
confidence: 55%
“…Of the six IGFBPs fully characterised, IGFBP-1 is considered to be the principal hour-to-hour regulator of circulating IGF activity [14], forming the link between dietary ingestion, glucose metabolism and the IGF axis. We and others have established close links between the IGF system and the development of impaired glucose tolerance, obesity and macrovascular disease [15][16][17][18]. In a white European population, we demonstrated that such changes predict the development of worsening glucose tolerance at the 5-year follow-up [6].…”
Section: Introductionsupporting
confidence: 55%
“…Our finding is consistent with a study suggesting that a polymorphism in the IGF-1 gene is associated with both low IGF-1 concentrations and an increased risk of type 2 diabetes. 23 Our study had several strengths, including a large sample size, the prospective design, the ability to assess risk associated with both diabetes treatment and some diabetic complications, and the ability to control for prior PSA testing as well as a large number of other potential confounding factors. Additionally, the observed number of prostate cancer cases was greater than the expected number for our cohort, based on the number and age distribution of this cohort and SEER rates.…”
Section: Discussionmentioning
confidence: 99%
“…It also calls for methods other than analyzing the "change" phenotypes to capitalize on longitudinal biomarkers. On the other hand, while high h 2 is important for predicting power for a genetic study, it does not, however, indicate how many and how strong the individual genetic factors are since the effects of all genes are pooled together (Vaessen et al 2001). …”
Section: Biochemical and Endocrine Serum Markersmentioning
confidence: 99%